Current approaches of nanomedicines in the market and various stage of clinical translation - Xiaoting Shan; Xiang Gong; Jie Li; Jingyuan Wen; Yaping Li; Zhiwen Zhang (Elsevier, 2022)
Compared with traditional drug therapy, nanomedicines exhibit intriguing biological features to increase therapeutic efficiency, reduce toxicity and achieve targeting delivery. This review provides a snapshot of nanomedicines that have been currently launched or in the clinical trials, which manifests a diversified trend in carrier types, applied indications and mechanisms of action. From the perspective of indications, this article presents an overview of the applications of nanomedicines involving the prevention, diagnosis and treatment of various diseases, which include cancer, infections, blood disorders, cardiovascular diseases, immuno-associated diseases and nervous system diseases, etc. Moreover, the review provides some considerations and perspectives in the research and development of nanomedicines to facilitate their translations in clinic.